A dry separation technique for improving the quality of coking coal middlings. Issue 3 (3rd March 2020) - Li, Zhen; Fu, Yanhong; Yang, Chao; Zhou, Anning; Yu, Wei; Liu, Lijun; Qu, Jinzhou; Zhao, Wei
ABSTRACT: To maximize the potential of China's scarce coking coal resources, we studied quality improvement techniques for coal middlings using a self-designed fluidized bed jet milling–fineness classification system. The middlings were obtained from the Xiqu coal preparation plant of the Shanxi Coking Coal Group. The results of this study show that the maximum ash gradient occurs between the classifier-I products and the bag filter products. The particle size and mineral content of the classified products decreased with classification. The lowest recorded sulfur content in these products was 1.32%, and the desulfurization rate reached a maximum of 42.36%. Classifier-I had the highest classification accuracy (0.60), which corresponds to the highest recorded value of the maximum ash gradient. The higher the classification accuracy, the better the separation effect. The cyclone process yielded improved products with high yields. Range and variance analyses of orthogonal tests revealed that both the rotation speed of classifier-II and the crushing pressure significantly affected the ash content of the cyclone products. The influence of the various process parameters on the yield of the cyclone products was insignificant. Using the jet milling–fineness classification system, we classified products by ash content, sulfur content, particle size, and separation accuracy cascade change, enabling the quality improvement and classification of coal products.